DNA barcoding of Aphelopus Dalman (Hymenoptera, Dryinidae) from China, with descriptions of four new species - Olmi, Massimo; Chen, Hua-Yan; Guglielmino, Adalgisa; Ødegaard, Frode; Vollaro, Massimo; Capradossi, Leonardo; Liu, Jing-Xian (European Journal of Taxonomy, 2022)
Species of the genus Aphelopus Dalman (Hymenoptera, Dryinidae) are important natural enemies of leafhoppers. The genus is relatively diverse in China, with 35 recorded species. In order to further make use of these important parasitoids in biological control programs, species of Aphelopus collected across China are studied using an integrative approach (combined DNA barcoding and morphology). Of the 17 studied species, two are newly recorded from China: A. nivealis Mita & Olmi, 2014 and A. prolatus Mita & Olmi, 2014, and four are described as new to science: A. incognitus Chen, Olmi & Guglielmino sp. nov., A. maculiala Olmi, Chen & Ødegaard sp. nov., A. taianensis Olmi, Ødegaard & Chen sp. nov., and A. zaifui Olmi, Chen & Liu sp. nov. The total number of Aphelopus species known from China is raised from 35 to 39. Keys to the Oriental and Eastern Palaearctic species of Aphelopus are modified to include the new species. Application of DNA barcoding in the species delimitation of Dryinidae is discussed.